Fatty Acids and Its Derivatives from the Extracts of Ficus mucoso Leaves - Abdulmumeen Amao Hamid; Godshelp Osas Egharevba; Shuaib Bolaji Issa; Oluwafeyikemi Mercy Olalere; Bukunmi Temitope Akinloye; Yakub Tunde Yakub; O. Sulyman Ibrahim; Idris Umar; Habeebulahi Ajibola Adekilekun; Idris Olatunji Sanusi; Abdullahi Alhaji Ahmad (Biology, Medicine, & Natural Product Chemistry, 2026)
The n-hexane, ethyl acetate and methanol extracts of Ficus mucoso leaves were screened for the presence of metabolites, using column and thin-layer chromatographic techniques. Dodec-6-enoic acid (1), methyl hexadecanoate (2), hexadec-9-enoic acid (3), and ethyl tetradecanoate (4) were obtained from the extracts of F. mucoso leaves. These compounds were confirmed via 1H and 13C Nuclear Magnetic Resonance Spectroscopy (NMR) and available published literature.